Research on carbon emissions during the construction process of prefabricated buildings based on BIM and LCA - Yang Ding; Zhen-Zhen Guo; Shuang-Xi Zhou; Yong-Qi Wei; An-Ming She; Jing-Liang Dong (Journal of Asian Architecture and Building Engineering)
The goal of double carbon reflects the new goals and requirements of China’s entry into a new development stage. In this regard, the construction industry, as a large producer of carbon emissions, should focus on emission reduction. In the whole life cycle of buildings, the carbon emission intensity in the physicochemical stage is the largest, so we should focus on the carbon emission in the physicochemical stage. Compared with the cast-in-situ concrete floor slab, the bidirectional prestressed precast hollow slab (BPPHS) has the characteristics of environment-friendly under the condition of meeting the building stress, and the manufacturing process of precast floor slab is more standardized, which can give full play to the performance of components. Based on BIM (Building Information Modeling) and LCA (Life Cycle Assessment) theory, and in the case of tram transportation, this paper studies the carbon emission of prefabricated hollow floor slab used in prefabricated buildings in the building stage. The research shows that the use of BPPHS reduces the carbon emission of 197,332.81 kg in the whole physicochemical stage, and the emission reduction rate is 46.52% compared with the cast-in-place slab. Compared with the ordinary prefabricated laminated plate, the emission reduction rate reaches 45.40%; The carbon emission sources in the materialization stage of prefabricated buildings are divided into production stage, transportation stage and construction stage. The carbon emission reduction in each stage accounts for 42.29%, 46.18% and 51.08%, respectively, in each stage of cast-in-situ floor slab. Compared with ordinary precast slab, the emission reduction rates of each stage are 34.67%, 53.60% and 47.84%, respectively. The emission reduction potential of BPPHS is very considerable. It can not only promote the development of prefabricated buildings but also have lower carbon than conventional precast slab. The study provides new ideas for reducing building carbon emissions, which will also provide reference for industry entrepreneurs and relevant governments to realize low-carbon economy and sustainable development.